Intervensi Inovasi Back Massage Terhadap Kelelahan Pada Pasien Di Ruang Intensive Cardiac Care Unit RSUD Aji Muhammad Parikesit Tenggarong - Ramlah, Ramlah; Wibowo, Thomas Ari; Astuti , Zulmah; Asyadi, Fitroh (Alauddin Scientific Journal of Nursing, 2025)
Congestive Heart Failure, also known as heart failure, occurs when the heart is unable to pump sufficient blood to meet tissue oxygen needs, resulting in an abnormal increase in heart pressure. Back massage is a form of nursing management that can be used to relieve heart failure patients' fatigue and other symptoms. The purpose of back massage, a soft tissue manipulation technique, is to help speed up the healing process for various diseases by relaxing muscles, increasing blood circulation, increasing flexibility, and eliminating pain. Objective: To analyze patients in the Intensive Cardiac Care Unit (ICCU), RSUD Aji Muhammad Parikesit Tenggarong with CHF, namely Innovative Back Massage. Method: Analyze this practice using the case study method with nursing care. The samples were patients who had a medical diagnosis of CHF with fatigue in the ICCU room. Research results: Based on the implementation of the Back Mass age innovation for 3 days with a duration of 5 minutes for each intervention, a decrease in fatigue scores was obtained, the average result for days 1 to 3 was 2.6. Conclusion: Based on the evaluation after the Back Massage therapy was carried out, it showed that there was a decrease in the fatigue score from a severe fatigue score to moderate fatigue. This is significant for heart failure sufferers, namely a diagnosis of CHF.